2003
DOI: 10.1097/01.tp.0000085652.47821.8a
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia after 95 right-lobe living-donor hepatectomies for liver transplantation is not a significant source of morbidity

Abstract: We, therefore, cannot endorse the routine administration of hyperalimentation with supratherapeutic phosphorus because of its potential morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Although some early reports have shown earlier and more severe recurrence of HCV following LDLT [26] compared to DD recipients [28], this issue is still highly controversial [27,29]. Recent data [27,30,31], including data from our patients [32], have shown that this may not be true. Given the current decrease in waiting list mortality with LDLT, we strongly feel that HCV cirrhosis potential recipients should be treated like any other potential recipients on the waiting list for LDLT.…”
Section: Recipient Considerationmentioning
confidence: 67%
“…Although some early reports have shown earlier and more severe recurrence of HCV following LDLT [26] compared to DD recipients [28], this issue is still highly controversial [27,29]. Recent data [27,30,31], including data from our patients [32], have shown that this may not be true. Given the current decrease in waiting list mortality with LDLT, we strongly feel that HCV cirrhosis potential recipients should be treated like any other potential recipients on the waiting list for LDLT.…”
Section: Recipient Considerationmentioning
confidence: 67%
“…In two retrospective cohort studies including respectively 35 and 44 patients undergoing major hepatectomies, 67% and 61.3% rates of HP were identified (13,14). In the living liver donor population, retrospective reports showed HP to occur in 65.9% to 70% of patients after right hepatectomy (15,25,26). We observed a slightly lower proportion of HP patients (55.5%), which can be related to larger sample size, routine post-operative repletion of phosphate, and/or inclusion of all extent of hepatectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported increased morbidity in patients with HP, including prolonged mechanical ventilation time and longer length of stay (13,14,25,26). They advocated for early and aggressive repletion of serum phosphate after hepatectomy to prevent surgical complications (13,14,25,26). With a sample size ten times larger than these previous studies, our study did not reveal a difference in post-operative morbidity between HP and NP (5.8% vs. 6.7%; P=0.56).…”
Section: Discussionmentioning
confidence: 99%
“…They are given parenteral magnesium and phosphate infusions until tolerating diet and then transitioned to oral supplementation as required [44,45]. Subcutaneous vitamin K (10 mg) is administered for the first 2-3 days after surgery depending on whether intraoperative i.v.…”
Section: Postoperative Managementmentioning
confidence: 99%